German picture Dictionary - Wilkes, Angela (National Text. Book Lincolnwood, IL, 1986)
The German Picture Dictionary is for everyone who is beginning to study German. Through it, you are introduced to 1,200 of the most commonly used words in both English and German.
9 - 12 years
Keywords: Visual dictionary -- German